A novel route to improve the mechanical and rheological properties of HTPE/AP/Al propellant by adding a modified hyperbranched polyester. (August 2021) - Wen, Xiaomu; Zhang, Ximing; Chen, Keke; Luo, Yunjun
Both better mechanical and rheological properties are pursued for composite solid propellant. In this work, varying proportions of a modified hyperbranched polyester (MHBPE) were added to HTPE/AP/Al propellant. The static tensile property as one kind of mechanical properties of MHBPE/HTPE/AP/Al propellant were found to be superior to those of blank HTPE/AP/Al propellant as a result of the entanglement and interpenetration of molecular chains caused by the introduction of the hyperbranched structure. Evaluations on the related improved creep resistance and stress relaxation performance further demonstrated the advantages of introduction of MHBPE to HTPE/AP/Al propellant. Rheological properties of HTPE/AP/Al propellant with and without MHBPE during the casting process were investigated and compared and the results confirmed the improvement benefiting from low viscosity and loose void structure. Thus, modified hyperbranched polyester provided a novel route to potentially meet the requirements for propellant manufacturing and applications.